Online banking wedding invitation card system / Rosliza Shaari - Shaari, Rosliza (2014)
The researchers are motivated to develop Online Booking Wedding Invitation Card because currently Atlantic Express Sdn Bhd Company still used the manually booking form to booking in the wedding card. The customer must come to the shop to make the booking and it take a time to the customer. The aim of this project is to develop Online Booking Wedding Invitation Card using Rapid Application Development (RAD). For this system researchers chooses one of the RAD methods which is prototyping technique. Prototyping technique are apply at design phase which is the prototype will build and demonstrate to the end user or stakeholder. And any changes can be made based on user need. We can refine the process that development process became easier because we a ready have guideline to develop the system which is developer can follow the prototype that has been agreed. There are three main objectives have been achieved, firstly identify the requirement of Online Booking Wedding Invitation Card System. Second is to design Online Booking Wedding Invitation Card System and lastly to develop and demonstrate of Online Booking Wedding Invitation Card System. Several methods have been applied for this research project which is interviewing the stakeholder to gather requirement and review related journals and articles for literature review. As the product, the system can help the administrator and moderate works and also can improve the booking wedding card and also the quality of works.